THE USE OF PICTURE SERIES TO IMPROVE STUDENTS’ WRITING ABILITY IN NEWS ITEM TEXT - Silfia, Efa (SJEE (Scientific Journals of Economic Education), 2018)
Abstract This study aims to explain whether picture series can improve students' abilities and describe the factors that influence changes in writing news item text using picture series. The research method used in this study is PTK (Classroom Action Research). The object of this research is class X students. The researcher uses 2 types of research instruments which are quantitative and qualitative. In quantitative, the researcher gives a writing test. While in qualitative, the researcher chose one of the teachers as a collaborator to observe and fill in the note field when the researcher taught during the research. Based on the results of the analysis data, the researchers obtained evaluation score I was 63.29 and evaluation II was 77.14. This shows that using picture series can improve students' writing skills. Factors that influence changes in students' writing ability using this media are visible from classroom management, media used by teachers, and learning methods.Keyword : Writing, News Item, Picture Series.